ANALISIS PUTUSAN HAKIM TERHADAP TINDAK PIDANA KORUPSI YANG DILAKUKAN DENGAN BERBARENGAN (Studi Putusan Nomor: 5/Pid.Sus-TPK/2021/PN.Mdn) - July Esther; Siahaan, Eko; Manullang, Herlina (Nommensen Journal of Legal Opinion, 2024)
Corruptions is a part of an unreliable moral attitude even reproached. Corruptions in a broad sense is not just in the form of misappropriating public money or state wealth, including corruptions loyalty. Loyalty to his family, wife, children, department and people of his electorate. Corruption by the regional head, for example, means not only making losses to the country so enriching it self but also directly affecting the distrust of its electorate population. The necessity of checking permits for regional officials, especially the head of the area suspected of being involved in corruptions is in fact a bizarre subject for investigators, so it is an obstacle for the prosecution and the Corruption Eradication Commission (CEC). The existence of the permit was actually narrowed down to the prosecution’s motion and the CEC investigated corruptions allegations.